Supplemental Vitamin D and Incident Fractures in Midlife and Older Adults - LeBoff, Meryl S.; Chou, Sharon H.; Ratliff, Kristin A.; Cook, Nancy R.; Khurana, Bharti; Kim, Eunjung; Cawthon, Peggy M.; Bauer, Douglas C.; Black, Dennis; Gallagher, J. Chris; Lee, I-Min; Buring, Julie E.; et al. (The New England journal of medicine, 2022)
A study ancillary to a large trial showed that supplemental vitamin D 3 did not lower the risk of fractures among generally healthy midlife and older adults not selected for vitamin D deficiency, low bone mass, or osteoporosis.